Conceptual representations in bicultural bilinguals: An ERP approach. Issue 5 (25th November 2021) - Pan, Xuan; Xiong, Andy; Jouravlev, Olessia; Jared, Debra
Abstract: We investigated conceptual representations for translation word pairs in bilinguals who learned their languages in different cultural contexts. Mandarin–English bilinguals were presented with a word, and then a picture, and decided if they matched. Both behavioural and ERP data were collected. In one session, words were in English and in another they were the Mandarin translations. Critical pictures matched the prior word and were either biased to Chinese or Canadian culture. There was an interaction of test language and picture type in RT and errors in the behavioural data, and in five components in the ERP data, indicating that the task was easier when the culture depicted in the picture was congruent with the language of the preceding word. These findings provide evidence that the specific perceptual experiences that bilinguals encounter when learning words in each language have an impact on the semantic features that are activated by those words.